When do Co‐located Firms Selling Identical Products Thrive?. (15th September 2022) - Bernhardt, Dan; Constantinou, Evangelos; Shadmehr, Mehdi
Abstract : When consumers only see prices once they visit stores, and some consumers have time to comparison shop, co‐location commits stores to compete and lower prices, which draws consumers away from isolated stores. Profits of co‐located firms are a single‐peaked function of the number of shoppers—co‐located firms thrive when there are some shoppers, but not too many. When consumers know in advance whether they have time to shop, effects are enhanced: co‐located stores may draw enough shoppers to drive the expected price paid by a non‐shopper below that paid when consumers do not know if they will have time to shop.